ACTG 260: a Randomized, Phase I-II, Dose-Ranging Trial of the Anti-Human Immunodeficiency Virus Activity of Delavirdine Monotherapy - Para, Michael F. (American Society for Microbiology, 1999)
ACTG 260 was an open-label, four-arm trial designed to study the safety and anti-human immunodeficiency virus (anti-HIV) activity of delavirdine monotherapy at three ranges of concentrations in plasma compared to those of control therapy with zidovudine or didanosine. Delavirdine doses were adjusted weekly until subjects were within their target trough concentration range (3 to 10, 11 to 30, or 31 to 50 μM). A total of 113 subjects were analyzed. At week 2, the mean HIV type 1 (HIV-1) RNA level declines among the subjects in the three delavirdine arms were similar (0.87, 1.08, and 1.02 log(10) for the low, middle, and high target arms, respectively), but by week 8, the subjects in the pooled delavirdine arms showed only a 0.10 log(10) reduction. In the subjects in the nucleoside arm, mean HIV-1 RNA level reductions at weeks 2 and 8 were 0.67 and 0.55 log(10), respectively. Because viral suppression by delavirdine was not maintained, the trial was stopped early. Rash, which was usually self-limited, developed in 36% of subjects who received delavirdine. Delavirdine monotherapy has potent anti-HIV activity at 2 weeks, but its activity is time limited due to the rapid emergence of drug resistance.